Current and emerging adjuvant therapies in biliary atresia - Fligor, Scott C.; Hirsch, Thomas I.; Tsikis, Savas T.; Adeola, Andrew; Puder, Mark (Frontiers in Pediatrics, 2022)
Following Kasai hepatic portoenterostomy (HPE), most patients with biliary atresia will eventually require liver transplantation due to progressive cirrhosis and liver failure. Preventing liver transplantation, or even delaying eventual liver transplantation, is the key to improving long-term outcomes. This review first examines the commonly used adjuvant therapies in post-HPE biliary atresia and the strength of the evidence supporting these therapies. Next, it examines the evolving frontiers of management through a comprehensive evaluation of both recently completed and ongoing clinical trials in biliary atresia. Promising therapies used in other cholestatic liver diseases with potential benefit in biliary atresia are discussed. Improving post-HPE management is critical to prevent complications, delay liver transplantation, and ultimately improve the long-term survival of patients with biliary atresia.